Perancangan Aplikasi Sistem Pendataan Penerima Pasar Murah Menggunakan Metode Extreme Programming - M Aji Fatroni; Ryci Rahmatil Fiska (Pusat Riset dan Inovasi Nasional, 2024)
The Cheap Market activity is one of the programs launched by the Bengkalis government to deal with price inflation of basic commodities which usually occurs during religious holidays such as Eis al-Fitr as well as Christmas and New Year. In implementing this program, there ware many difficulties and obstacles faced by the Bengkalis Trade and Industry Service as the implementer of cheap market activities. To deal with the obstacles currently being faced, the author created a website-based Cheap Market Data Collection System Application (SIPEMURAH). The SIPEMURAH application was created using the extreme programming method whichhas 4 stages, namely planning, design, coding dan testing. By using this method the developer must be prepared for changes to be made if the application being built does not meet the user’s widhes, then testing is carried out using the Blackbox testing technique to get good result.